PENERAPAN KURIKULUM 2013 DALAM MENINGKATKAN KETERAMPILAN, SIKAP, DAN PENGETAHUAN - Otang Kurniaman; Eddy Noviana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
Implementation of the 2013 curriculum is very different from the previous curriculum, there are still many obstacles that we know greatly affect the learning outcomes, both in terms of media used, the assessment in the 2013 curriculum is more complicated than the previous curriculum then the methods used to convey the learning materials that want to be taught not effective or even incompatible with the material to be conveyed. This research method is a classroom action research conducted in improving the learning process, with four meetings. The assessment taken in this study is an evaluation evaluation of each meeting in the form of attitudinal value, value of knowledge and skill value based on teacher's book on theme 4 "Healthy is Important" with sub theme 1 "Importance of Health and Environment". On the attitudes that appear attitude of self-confidence, curiosity and independence Already entrusted by 20.68% confidence, and curiosity while mandated 6.2% lower because students are still not familiar with the implementation of the curriculum 2013. Results of student knowledge seen the development in excellent value at the first meeting of 36.4%, at the second meeting decreased to 30.3%, while at the third meeting experienced a 52.25% increase again. While on the results of these students' skills on four meetings emerged every meeting with a very good category at the first meeting of 18.1%, at the second meeting increased to 27.3%, the third meeting decreased to 20.68%, while at the fourth meeting increased again by 65.62%.